Use of software: a necessity in the Mathematics’s teaching? - Sanabria Brenes, Giovanni (Atenas, 2016)
Régine Douady states that in order to build an acceptable mathematical notion, it is necessary that teachers address their teaching through problems involving at least two frames: geometric, algebraic, numeric, ...Since a concept makes sense for through problems, functioning through different frameworks which achieve its meaning. How important is the use of software in the game frames? This paper presents evidence on which the software becomes essential to solving problems in a given frame. Given this background, will you be teaching mathematics outdated?